AUTO DOOR SENSOR DESIGN USING INFRA RED - T. Edi Johan; Jalinas. Skom. MM Jalinas. Skom. MM (Jurnal Sistem Komputer, 2001)
Infrared is light that can not be seen with the naked eye. Infrared is located outside ofthe red part of the visible spectrum. Significantly different wavelengths in the visiblelight between 650 nm and 700 nm. While the infrared ray wavelength is 700 nm and900 nm.Termsuk infrared ray electromagnetic waves. Electromagnetic waves including awave that has medn transfersal magnetic and electric fields rambatnya directionperpendicular to each other.Ease contained in the infra-red can not be seen naked eye, can penetrate theatmosphere, does not require a lot of stress and other causes are used for variousindustrial purposes, commercial and military.